Applicability of environmental management systems to building companies - Degani, Clarice Menezes (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The application of environmental management systems to building companies is becoming more frequent due to the necessity of considering the environmental impacts of construction activities on the physical, biotic and socio-economic environment, as well as to the interest resulting from some external factors, such as the existence of adequate environmental solutions for the reduction of its negative impacts. A literature review and the field research conducted on two Brazilian firms illustrate the trend of implementing sustainable construction and provide evidences that environmental management systems are applicable to building companies. Some benefits resulting from the applicability of environmental management systems to those companies are discussed, not only for the environment but also for the firms themselves, from the strategic, operational and financial perspectives. Moreover, some difficulties and success factors in the implementation of such systems are identified.